KONSEP BIMBINGAN DAN KONSELING SPIRITUAL: KERANGKA KERJA UNTUK GURU BIMBINGAN DAN KONSELING - Ujang Saprudin (Universitas Sultan Ageng Tirtayasa, 2019)
Abstract This study purposed to find the concept of guidance and counseling based on the verses of the Qur'an, which is about the nature of human beings, good and bad attitude with all problems and solutions. The essence of Islamic teachings is to teach monotheism, peace, akhlakul karimah (personality with character). The form of this study is a qualitative library research, the main idea in this literature study is an integrated framework as a reference for the counseling process in guiding students based on the verses of the Qur'an so that students are able to overcome the problem so that students have a tendency being good at determining attitude assessment in the 2013 curriculum. The results of this study concluded: Bahwamanusia is essentially a biological, personal, social, and spiritual being. Good attitude is the tendency of personal behavior that is able to regulate themselves in relation to themselves, others, the environment, and Allah SWT. Bad attitude is the tendency of personal behavior that is not able to regulate themselves in relation to themselves, others, the environment, and Allah SWT. Keywords: Guidance and spiritual counseling, BK service strategies at school.